Characteristics of Boarding School Curriculum at Integrated-Islamic Junior-High School Ibnu Abbas Klaten In The Academic Year of 2011/2012 - Iswahyuni, Iswahyuni, Prof. Dr. Yetty Sardjono, M.Si, Dr. Phil. Dewi Candraningrum, M.Ed (2013)
The purposes of this study are to describe the characteristics of the program and the content of the boarding school curriculum at Integrated-Islamic Junior High School Klaten Ibnu Abbas. The results suggested that Integrated-Islamic Junior High School Ibnu Abbas is one of the school-based boarding school where the school used a model curriculum that combines school curriculum (Education), JSIT (Network of Integrated Islamic School), that the curriculum of schools with schools to develop the curriculum by using the basic curriculum signposts that have been established by the foundation. Boarding school curriculum in Integrated-Islamic Junior High School Ibnu Abbas Klaten, refers to the government regulation number 19 of 2005 of the national standards, article 6, paragraph 1, consists of a group of subjects and noble religion, nationality and personality, science and technological, aesthetic, and physical lessons, sports and health. Curriculum structure in Integrated-Islamic Junior High School Ibnu Abbas Klaten held for 42 hours of lessons in one week with a duration of 40 minutes, plus 4 additional hours to Religious lessons, and 4 hours for Arabic and Al Quran. Local content carried by boarding with features to accommodate local culture, so that the local content include: Tahfidzul Quran, Arabic, and Javanese.